Prophet Muhammad (PBUH) Business Management In Organizational Development (Case Study Of Wikrama-Bogor Vocational School). - Niati, Niati; Tanjung, Hendri; Yasid, Mukhamad (Jurnal Manajemen, 2020)
Global business in the industrial sector has an important role in Indonesia’s national economy. One of the organizations that support the development of business sector and also serving a noble purpose is the educational institution. This institution can address the needs of business sector for adequate human resources that capable in both hard and soft skill and has the ability to address the challenge as well as using the opportunity to develop the business. A business model is required in order to achieve an optimum result without sacrificing the stakeholder, one that upholds the value of religion and faith. Prophet Muhammad (pbuh) business management model is a model that has been proven to be successful for his business, a model in which the business can strive through his personality of shiddiq, amanah, fathonah, and tabligh. The objective of this research is to study the implementation of Prophet Muhammad (pbuh) business model that translates the value of shiddiq, amanah, fathonah, and tabligh into organizational development. The study was conducted in Wikrama-Bogor Vocational School by qualitative and case study approach. Data sampling was acquired through interviews, observation, questionnaire, and documentation. The population was 1,704 people and the total sample used in the analysis were 410 respondents. The result of this research shows that the implementation of shiddiq, amanah, fathonah, and tabligh values as the manifestation of Prophet Muhammad (pbuh) business management in Wikrama-Bogor Vocational School organizational development is in the good category. The score of 4 (four) Prophet Muhammad (pbuh) business management variables is greater than 55% which is the threshold for the good category. Therefore the value of honesty, sincerity, transparency, modesty, and objective as indicators that represent the value of shiddiq has been well implemented in Wikrama-Bogor Vocational School. The implementation of amanah value through the principles of respect, authority, trust, and dignity is also in the good category. The implementation of fathonah value through intelligence, knowledge, ethics, professionalism and reality indicator shows a similar result. The implementation of tabligh value through communication, leadership, wisdom, information and good example also is well implemented.